2020
DOI: 10.1038/s41467-020-14463-1
|View full text |Cite
|
Sign up to set email alerts
|

Chiral terahertz wave emission from the Weyl semimetal TaAs

Abstract: As a fascinating topological phase of matter, Weyl semimetals host chiral fermions with distinct chiralities and spin textures. Optical excitations involving those chiral fermions can induce exotic carrier responses, and in turn lead to novel optical phenomena. Here, we discover strong coherent chiral terahertz emission from the Weyl semimetal TaAs and demonstrate unprecedented manipulation over its polarization on a femtosecond timescale. Such polarization control is achieved via the colossal ultrafast photoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 53 publications
(104 reference statements)
2
111
2
1
Order By: Relevance
“…Numerous theoretical and experimental studies have revealed that the chiral fermions can host rich fascinating physical phenomena, such as the chiral zero sound [39,40], colossal chiral ultrafast photocurrents [41], and photoinduced anomalous Hall effects [42]. Our discovery introduces a new degree of freedom to study the chiral fermions, which would facilitate uncovering more exotic behaviour associated with the chiral fermions in materials.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous theoretical and experimental studies have revealed that the chiral fermions can host rich fascinating physical phenomena, such as the chiral zero sound [39,40], colossal chiral ultrafast photocurrents [41], and photoinduced anomalous Hall effects [42]. Our discovery introduces a new degree of freedom to study the chiral fermions, which would facilitate uncovering more exotic behaviour associated with the chiral fermions in materials.…”
Section: Discussionmentioning
confidence: 86%
“…We observed THz emission in the midinfrared regime (0.2-0.5 eV). We expect that the development of broadband THz emission spectroscopy provides the opportunity to reveal bulk photovoltanic 23,24,61 and spintronic responses 71 in a low-energy regime and also the possibility of probing Berry curvature in surface-state photogalvanic effect in topological insulators 72 .…”
Section: Cpge Calculationmentioning
confidence: 99%
“…The Weyl semimetal phases discovered in materials of the transition monopnictide family such as TaAs [10][11][12][13][14][15][16][17] lack inversion symmetry, which allows for nonzero second-order nonlinear optical responses and has motivated the search for topological responses using techniques of nonlinear optics. This search has resulted in the observation of giant second-harmonic generation (SHG) 18,19 , as well as interesting photogalvanic effects [20][21][22][23][24] . However, neither response can be directly attributed to the topological charge of a single band crossing, since mirror symmetry-present in most known Weyl semimetals-imposes that charges with opposite sign lie at the same energy and thus contribute equally 19,25 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, highly efficient chiral terahertz emission with elliptical polarization states has been obtained from the fascinating topological phase matter, bulk Weyl semimetal TaAs with reflection terahertz emission geometry. 22 Inspired by these pioneering breakthroughs, the question of whether we can utilize the spin freedom of electrons to generate and manipulate spin-polarized terahertz waves has become very interesting.…”
Section: Introductionmentioning
confidence: 99%